2021
DOI: 10.2478/pielxxiw-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Personal wellbeing and stress coping strategies among nurses working at the departments of anesthesiology and intensive care

Abstract: Aim. To investigate the personal wellbeing of nurses in relation to selected variables. Then to explore whether personal wellbeing has any impact on preference for stress coping strategies. Material and methods. The sample consisted of 509 nurses working at the Department of Anaesthesiology and Intensive Medicine. We used the Personal Wellbeing Index – Adult (PWI – A) scale and coping strategies (Brief COPE) questionnaire. Data were analyzed using the methods of descriptive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The nature of the stressful situation, the individual's personality, and the social context can all influence which particular coping strategy is used. The results of some studies have shown that adopting a specific coping strategy relates to factors such as gender [36][37][38][39], age [37,[40][41][42], marital status [40,43], work experience [40,44], shift work [45,46], and workplace [37,47]. Perhaps the reported contradictions can be related to the difference in occupational, situational, cultural, and social conditions, which indicates the need for further investigation in different cities and occupations, especially high-stress jobs.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the stressful situation, the individual's personality, and the social context can all influence which particular coping strategy is used. The results of some studies have shown that adopting a specific coping strategy relates to factors such as gender [36][37][38][39], age [37,[40][41][42], marital status [40,43], work experience [40,44], shift work [45,46], and workplace [37,47]. Perhaps the reported contradictions can be related to the difference in occupational, situational, cultural, and social conditions, which indicates the need for further investigation in different cities and occupations, especially high-stress jobs.…”
Section: Discussionmentioning
confidence: 99%